1976
DOI: 10.1042/bj1530141
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of pepsinogen into pepsin is not a one-step process

Abstract: By incubation of pepsinogen with pepstatin at pH2.5, the first 'active' protein generated on activation is trapped in an inactive complex. The first activation peptide liberated has been identified as residues 1-16 from the pepsinogen sequence. This suggests a sequential mechanism rather than a one-step formation of pepsin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
21
1
2

Year Published

1979
1979
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 10 publications
3
21
1
2
Order By: Relevance
“…This showed that the exogenous pepsin attacked the pepsinogen The activation of porcine pepsinogen A in solution proceeded through two different pathways, i.e. one-step pathway and a sequential pathway [2,5,61. As shown in Fig.…”
Section: ~I Y K V P L V R K K S L R R N L S E H G L L K D F L K K H Nmentioning
confidence: 99%
See 1 more Smart Citation
“…This showed that the exogenous pepsin attacked the pepsinogen The activation of porcine pepsinogen A in solution proceeded through two different pathways, i.e. one-step pathway and a sequential pathway [2,5,61. As shown in Fig.…”
Section: ~I Y K V P L V R K K S L R R N L S E H G L L K D F L K K H Nmentioning
confidence: 99%
“…1). This pathway has also been shown to occur in the activation of porcine [2], rabbit [3] and chicken [4] pepsinogens A, although in porcine and rabbit pepsinogens sequential pathways occurred simultaneously [2,3,5,6]. Contrary to these pepsinogens, the activation of bovine prochymosin [7], and human …”
mentioning
confidence: 99%
“…The two activation segments show a pronounced homology, especially in the first 27 amino acid residues (Fig.l), but in spite of this, peptides of different sizes are released during the initial limited proteolysis. During activation of porcine pepsinogen at pH 2 the bond Leu-Ile (18 -19) is cleaved first [6,7] while the peptide comprising residues 1 -27 was isolated after activating prochymosin at pH 2 [8]. Furthermore, as another difference from the activation of prochymosin, Bustin and ConwayJacobs [9] and Al-Janabi et al [lo] have found that the conversion of porcine pepsinogen into pepsin occurs mainly as an intramolecular (first-order) reaction at pH 2.…”
mentioning
confidence: 99%
“…The formation of a metastable intermediate during the activation process appears to indicate that the activation of procathepsin D-I1 occurs in two steps. A similar type of activation has also been suggested in the case of porcine pepsinogen [27,28]. Procathepsin D-I1 apparently showed an increasing affinity to pepstatin-Sepharose, as the pH was decreased from 5 to 3.…”
Section: Discussionmentioning
confidence: 69%